2009
DOI: 10.1007/s00277-009-0706-x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between leukocytosis and thrombosis in Philadelphia-negative chronic myeloproliferative neoplasms

Abstract: International audienceThe evidence that leukocytes may contribute to the pathogenesis of thrombosis in Chronic Myeloproliferative Neoplasms is increasing but not definitive. To further enforces whether an increased leukocyte count is associated with thrombosis and whether this effect can be modulated by cytoreductive therapy, we analyzed the clinical course of 187 patients with Polycythemia Vera (PV) and Essential Thrombocythemia (ET) followed at two Italian Institutions over a period of 7 years. The associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 22 publications
2
19
0
1
Order By: Relevance
“…10,12,15,16 This study confirms previous observations on the association between leukocytosis and worse survival in ET. 10,12,16 The role of leukocytosis on thrombosis prediction in ET has been largely discussed in the last years as many investigators found a correlation with thrombosis, 3,[17][18][19][20] others did not, 21,22 and others found a relationship between increase of leukocyte count over time and thrombosis. 23 Although all of these factors should ideally be assessed in a prospective study, the IPSET model undoubtedly states that leukocytosis Ͼ 11 ϫ 10 9 /L is a predictor of survival as well as history of thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…10,12,15,16 This study confirms previous observations on the association between leukocytosis and worse survival in ET. 10,12,16 The role of leukocytosis on thrombosis prediction in ET has been largely discussed in the last years as many investigators found a correlation with thrombosis, 3,[17][18][19][20] others did not, 21,22 and others found a relationship between increase of leukocyte count over time and thrombosis. 23 Although all of these factors should ideally be assessed in a prospective study, the IPSET model undoubtedly states that leukocytosis Ͼ 11 ϫ 10 9 /L is a predictor of survival as well as history of thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…JAK2 V617F is associated with a higher incidence of thrombotic events [28,29,34,35]. In addition, patients bearing the JAK2 V617F mutation have higher hemoglobin levels, and higher WBC and lower platelet counts [34].…”
Section: Discussionmentioning
confidence: 99%
“…The WBC count was found to be an independent risk factor for thrombosis in MPN patients [29,30,31,32]. …”
Section: Discussionmentioning
confidence: 99%
“…(10,11). Bazal lökosit sayısı ve mutant JAK2 allel yükü göz önüne alınarak hastalık risk analizinin yapılacağı prospektif çalışmalara ihtiyaç vardır.…”
Section: İnterferon Alfaunclassified